The Relation Between Skill Levels and the Cyclical Variability of Employment, Hours, and Wages - Keane, Michael (IMF Working Papers; Working Paper, 1993)
This paper uses micro panel data to examine differences in the cyclical variability of employment, hours, and real wages for skilled and unskilled workers. Contrary to conventional wisdom, we find that, at the aggregate level, skilled and unskilled workers are subject to essentially the same degree of cyclical variation in wages. However, important differences emerge in the patterns of employment and hours variation for skilled versus unskilled workers, especially when a college degree is used as a proxy for skills. We find that the quality of labor input per manhour tends to rise in recessions, thereby inducing a countercyclical bias in aggregate measures of the real wage. We also find substantial differences across industries in the cyclical variation of employment, hours, and wage differentials, which we interpret as indicative of important inter-industry differences in labor contracting.